Allergens of the imported fire ant - Nordvall, S.L.; Johansson, S.G.O.; Ledford, D.K.; Lockey, R.F. (Journal of allergy and clinical immunology, 1988)
A whole body extact (WBE) was prepared by saline extraction of ground imported fire ants (IFA). A serum pool from rabbits immunized with the WBE elicited 31 precipitates on crossed immunoelectrophoresis. Crossed radioimmunoelectrophoresis was performed with sera from 26 RAST IFA-positive subjects, 24 of whom were known for clinical hypersensitivity to IFA and two subjects, known to be hypersensitive to yellow jacket. Radiostaining was obtained to 14 precipitates, some of which were judged to be partially identical. Thus, six apparently different allergen groups could be identified. Two of these fulfilled arbitrary criteria of major allergens. Three of the IFA WBE allergens were easily identified in crossed immunoelectrophoresis of a commercially obtained IFA-venom preparation. Sodium dodecyl sulfate-poly acrylamide gel electrophoresis of the IFA WBE demonstrated protein bands with molecular weight ranging from 10,000 to 200,000 daltons. An immunoblotting technique with nitrocellulose paper strips revealed binding of human IgE from hypersensitive subjects to four different bands (either single bands or clusters of proteins of similar molecular weight) with molecular weights ranging from 13,000 to 42,000 daltons. It is a notable finding that these insect allergens thus were of a similar size as important aeroallergens.